2020
DOI: 10.3390/molecules25040812
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Profile of the Genista tridentata L., a Species Used Traditionally to Treat Inflammatory Processes

Abstract: Ethnopharmacological surveys on Portuguese flora reveal that Genista tridentata L. is a shrub used in traditional medicine for the treatment of various inflammation-related health problems, although scientific support of its benefits is still necessary. In order to establish the anti-inflammatory potential of G. tridentata and support its traditional use, ethanolic extracts of three sections of the plant (root, stem, and leaves) were subjected to in vitro evaluation of anti-inflammatory activity using lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…The seeds extract comprises two peaks, at 7.72 and 7.92 min (Figure 1b), identified as caffeoylshikmic acid and taxifolin glucoside, respectively (Table 2). In both cases, the fragment pattern is analogous to previously reported data (Faustino et al., 2018; Simões et al., 2020), allowing their unequivocal identification.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The seeds extract comprises two peaks, at 7.72 and 7.92 min (Figure 1b), identified as caffeoylshikmic acid and taxifolin glucoside, respectively (Table 2). In both cases, the fragment pattern is analogous to previously reported data (Faustino et al., 2018; Simões et al., 2020), allowing their unequivocal identification.…”
Section: Resultssupporting
confidence: 87%
“…In the case of delphinidin 3‐ O ‐glucoside, the pseudomolecular ion [M‐H] − ( m/z 464) is detected, as well as the expected fragment ion at m/z 302 due to the loss of the glucose unit ([M‐H‐glucose] − ) (Strugała et al, 2016) and the fragment ion at m/z 285 due to the loss of the O ‐glucose unit ([M‐H‐ O‐ glucose] − ). Other typical glucose fragmentation, such as [M‐H‐C 3 H 6 O 3 ] − ( m/z 374) and [M‐H‐C 4 H 8 O 4 ] − ( m/z 344), were also observed (Simões et al., 2020).…”
Section: Resultsmentioning
confidence: 90%
“…Hot water Antioxidant (TABARS, IC 50 = 8.4 ± 0.2 µg/mL; OxHLIA, IC 50 = 37.7 ± 0.9 µg/mL) TBARS inhibition Oxidative haemolysis inhibition [31] Flowers Hydromethanolic Antifungal (Candida albicans, 10 mm inhibition zone; Candida glabrata, 11 mm inhibition zone) Disc diffusion test [32] Aerial parts Hydromethanolic Antibacterial (Staphylococcus aureus, MIC = 39.1 µg/mL) Microplate bioassay [33] Flowers Hot water Antimicrobial (Escherichia coli, MIC = 0.5 mg/mL; Salmonela typhimurium, MIC = 1 mg/mL; Bacillus cereus, MIC = 1 mg/mL; Listeria monocytogenes, MIC = 1 mg/mL; Aspergillus niger, MIC = 8 mg/mL; Aspergillus versicolor, MIC = 0.5 mg/mL; Penicillium funiculosum, MIC = 0.5 mg/mL; Penicillium verrucosum, MIC = 0.5 mg/mL) LPS-induced transcription of pro-inflammatory genes IL-1β, Nos2, Ptgs2, IL-6, and TNF-α; Western blot analysis [8,35] AA, antioxidant activity; GI 50 , values correspond to the concentration that causes 50% inhibition of cell proliferation; IC 50 , values corresponded to the extract concentration that inhibits in 50% the oxidation and inflammatory process; MIC, minimum inhibitory concentration.…”
Section: Flowersmentioning
confidence: 99%
“…Other evaluations, such as antifungal [32], antibacterial [31,33] agents, cytotoxicity activity in tumor and non-tumor cells [31], and even the immunostimulatory activity of the G. tridentata polysaccharides [34] were also performed. Additionally, Ferreira et al also performed in vivo and in vitro toxicological assays and concluded that short-term use is safe [8,28].…”
Section: Flowersmentioning
confidence: 99%
See 1 more Smart Citation